Effect of Mineral and Humic Substances on Tailing Soil Properties and Nutrient Uptake by Pennisetum purpureum Schumach - Adhe Phoppy Wira Etika; Rahmat Hasan (UNIVERSITY OF LAMPUNG, 2015)
Tin mining produces a by-product sand tailing from soil leaching with characteristic low pH and total organic carbon, and can be reclaimed by providing a suitable ameliorant. When available in situ, ameliorant materials can be economically used as they are required in large amounts. Fortunately, Bangka Belitung has sample stock of such kaolinite-rich minerals that can be utilized for improving soil chemical properties. Extracted organic materials, such as humic substances, can also be utilized as they influence the complex soil reactions, and promote plant growth. Thus, this study aimed to assess the effects of mineral, humic materials and interaction of both material on soil chemical properties and nutrient uptake of Pennisetum purpureum Schumach. A completely randomized design with 2 factors and 3 replications each was employed. Factor 1 was mineral matter is 0; 420; 840; 1.260 Mg ha-1 while Factor 2 was humic material is 0; 0.46; 0.92; 1.38 kg C ha-1. Air-dried samples of tailing were applied with oil palm compost then mixed evenly with mineral and humic materials. Penissetum purpureum Schumach was planted after 4 weeks incubation, and maintained for another 4 weeks. The results demonstrated that the addition of mineral matter significantly increased soil organic carbon content, total N, exchangeable K, Fe, Mn and boosted nutrient - total Ca, Mg and Mn – uptake of the plant. But the application of humic material increased only soil organic carbon content. The interaction of both materials only lowered soil pH.